2023
DOI: 10.3390/cimb45100489
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange and Multiple Sclerosis Dysregulations: Focus on the Removal of Pathogenic Circulatory Factors and Altering Nerve Growth Factor and Sphingosine-1-Phosphate Plasma Levels

Dimitar Tonev,
Albena Momchilova

Abstract: Multiple sclerosis (MS) is predominantly an immune-mediated disease of the central nervous system (CNS) of unknown etiology with a possible genetic predisposition and effect of certain environmental factors. It is generally accepted that the disease begins with an autoimmune inflammatory reaction targeting oligodendrocytes followed by a rapid depletion of their regenerative capacity with subsequent permanent neurodegenerative changes and disability. Recent research highlights the central role of B lymphocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 174 publications
0
11
0
Order By: Relevance
“…Most patients received three TPE procedures in LVPE mode (patients 1, 2, 3, 5), whereas one of them received four nanomembrane-based TPE procedures in LVPE mode (patient 4). We observed an elevation in NGF plasma levels in all patients (Figure 7) [143]. The measurement of OS markers (ROS and isoprostanes) showed that the application of TPE leads to a reduction in the OS level (Figures 8 and 9) [17], which is favorable for the general and neurological status of patients.…”
Section: The Role Of Tpe As An Os Modulatormentioning
confidence: 75%
See 4 more Smart Citations
“…Most patients received three TPE procedures in LVPE mode (patients 1, 2, 3, 5), whereas one of them received four nanomembrane-based TPE procedures in LVPE mode (patient 4). We observed an elevation in NGF plasma levels in all patients (Figure 7) [143]. The measurement of OS markers (ROS and isoprostanes) showed that the application of TPE leads to a reduction in the OS level (Figures 8 and 9) [17], which is favorable for the general and neurological status of patients.…”
Section: The Role Of Tpe As An Os Modulatormentioning
confidence: 75%
“…Translating the results of this preclinical model to the real clinical setting is achievable through the application of TPE in the treatment of acute exacerbations of MS. Through this non-pharmacological therapeutic approach, both an increase in circulating levels of NGF and a modulation of OS can be achieved [17,143]. Evidence for this will be presented in the next section.…”
Section: The Role Of Ngf As An Endogenous Nrf2 Activatormentioning
confidence: 99%
See 3 more Smart Citations